The Digital Divide: A Qualitative Study of Technology Access in Rural Communities - Tahmasebi, Farrokh (AI and Tech in Behavioral and Social Sciences, 2023)
This study aimed to explore the nature and implications of the digital divide in rural communities, identifying the key barriers to digital access and utilization. It sought to understand the socioeconomic, educational, and infrastructural factors contributing to the divide and to propose targeted interventions for bridging the gap. A qualitative research design was employed, utilizing semi-structured interviews with 20 participants from various rural communities. The interviews were designed to capture in-depth insights into participants' experiences with digital access and usage. Data were analyzed using thematic analysis to identify common themes and patterns related to the digital divide. The study revealed that economic barriers, inadequate educational resources, and insufficient infrastructure significantly hinder digital access in rural areas. Economic challenges include the affordability of devices and services, while educational barriers encompass both the availability of digital literacy programs and the reliance on schools for digital access. Infrastructure issues, notably internet connectivity and reliability, further exacerbate the digital divide. Additionally, the study highlighted the importance of tailored financial and educational services to support rural communities. Bridging the digital divide in rural communities requires a multifaceted approach that addresses economic, educational, and infrastructural barriers. Targeted policy interventions and collaborative efforts between stakeholders are crucial for enhancing digital inclusion and ensuring equitable access to technology for rural populations. The findings underscore the need for comprehensive strategies that go beyond improving connectivity to foster meaningful digital engagement and utilization.